2022
DOI: 10.3389/fmicb.2022.962146
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis to examine whether nitrification inhibitors work through selectively inhibiting ammonia-oxidizing bacteria

Abstract: Nitrification inhibitor (NI) is often claimed to be efficient in mitigating nitrogen (N) losses from agricultural production systems by slowing down nitrification. Increasing evidence suggests that ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) have the genetic potential to produce nitrous oxide (N2O) and perform the first step of nitrification, but their contribution to N2O and nitrification remains unclear. Furthermore, both AOA and AOB are probably targets for NIs, but a quantitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 96 publications
1
7
0
Order By: Relevance
“…Although the incubation conditions used in this study might have altered the proportion of AOB/comammox and AOA activities compared to the more competitive interactions observed in whole soil incubations (Prosser and Nicol 2012 , Rütting et al 2021 ). This trend of higher NI efficacy in more neutral soils, where net nitrification potential is AOB driven, compared to AOA dominated or more ASs has been observed previously (Guardia et al 2018 , Lu et al 2019 , Lei et al 2022 ).…”
Section: Discussionsupporting
confidence: 83%
“…Although the incubation conditions used in this study might have altered the proportion of AOB/comammox and AOA activities compared to the more competitive interactions observed in whole soil incubations (Prosser and Nicol 2012 , Rütting et al 2021 ). This trend of higher NI efficacy in more neutral soils, where net nitrification potential is AOB driven, compared to AOA dominated or more ASs has been observed previously (Guardia et al 2018 , Lu et al 2019 , Lei et al 2022 ).…”
Section: Discussionsupporting
confidence: 83%
“…In general, AOB tends to dominate nitrification in neutral and alkaline soils, while AOA is more prevalent in acidic environments [106]. Increasing the NH 4 + concentrations can enhance the nitrification activity of AOB [106], while AOA prefers environments with lower NH 4 + concentrations. Furthermore, many studies showed that NIs effectively decreased the AOB population but not AOA [30,65,106].…”
Section: Impacts Of Nitrification Inhibitor Usagementioning
confidence: 96%
“…However, results have been inconsistent [30]. In general, AOB tends to dominate nitrification in neutral and alkaline soils, while AOA is more prevalent in acidic environments [106]. Increasing the NH 4 + concentrations can enhance the nitrification activity of AOB [106], while AOA prefers environments with lower NH 4 + concentrations.…”
Section: Impacts Of Nitrification Inhibitor Usagementioning
confidence: 99%
See 1 more Smart Citation
“…3,4-dimethylpyrazole phosphate (DMPP) is a highly soluble compound with high stability and persistent suppression effects ( Li et al, 2023 ). Studies have shown that DMPP effectively inhibited the metabolic activity of AOB rather than AOA, which in turn led to a reduction of nitrification rate ( Lei et al, 2022 ). Furthermore, in calcareous soils where the nitrification process was regulated by AOB, the addition of DMPP significantly suppressed N 2 O emissions ( Bai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%